A new species of the leafhopper genus Neoreticulum Dai in China (Hemiptera: Cicadellidae: Deltocephalinae), with a key to species - Dai, Ren-Huai; Xing, Ji-Chun; Li, Zi-Zhong (Zootaxa, 2012)
The deltocephaline genus Reticulum, of tribe Athysanini, was established by Dai, Li & Chen (2006) with Reticulum transvittatum Dai, Li & Chen, 2006 as its type species. Dai & Zhang (2008) reviewed this genus and described two new species: R. trispinosum and R. lanceolatum from China. Recently, Dai (2009) proposed a new replacement name Neoreticulum to Reticulum Dai, Li & Chen, 2006 because the latter is a junior homonym of Reticulum Schröder, Medioli & Scott, 1989, and made three new combinations.